2018
DOI: 10.1007/s40091-018-0211-3
|View full text |Cite
|
Sign up to set email alerts
|

Numerical method for analysis and design of isolated square footing under concentric loading

Abstract: Footing is an important part of a structure, because its repair is extremely difficult and cumbersome. Therefore, all structural parameters should be carefully considered when designing a footing. An isolated footing needs sufficient depth, when considering the fixed base assumption. Extensive research has previously been conducted to define and formalize the depth of a rigid footing, i.e., the depth required, such that footing behaves as a rigid. Alternatively, working stress method (WSM) and limit state meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…If c 1 /2 is replaced by 鈭抋 1 /2 and the addition of P u1 a 1 /2 + M uy1 into Equation (17) to obtain the moment about the axis formed by q 2 and q 6 , the moment Mq 2 q 6 = 0. c.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If c 1 /2 is replaced by 鈭抋 1 /2 and the addition of P u1 a 1 /2 + M uy1 into Equation (17) to obtain the moment about the axis formed by q 2 and q 6 , the moment Mq 2 q 6 = 0. c.…”
Section: Resultsmentioning
confidence: 99%
“…Several models have been developed for the comprehensive design of reinforced concrete for circular, square and rectangular isolated footings subjected to biaxial bending [15][16][17][18][19][20]. Likewise, models for combined footings have been investigated for the complete design of reinforced concrete under biaxial bending in each column of trapezoidal-shaped [21], rectangular [22], L or corner [23], strap [24] and T [25] footing.…”
Section: Introductionmentioning
confidence: 99%
“…Simulating strip footing was possible using a beam element [23][24][25] that possessed both bending stiffness (EI) and axial stiffness (EA). The material model for this element was linear elastic, and its characteristics were dependent on specific parameters.…”
Section: Strip Footingmentioning
confidence: 99%
“…A number of investigators [21,22] remarked that geocell confinement in soil induces apparent cohesion, whereas the reinforcement depth is replaced by an equivalent layer, with homogenous properties [33]. The induced cohesion in the soil is related to the increase in the confining pressure on the soil due to the geocell reinforcement, which is calculated through the following equation:…”
Section: Parametric Calculations Of Reinforced Soil Propertiesmentioning
confidence: 99%
“…Less and more amounts of sand make the domination role for clay cohesion or friction between the sand particles in determining the shear strength of the mixture, respectively [19]. Numerical simulations demonstrated that the best redistribution of the load is achieved if reinforcements are placed up to a certain depth depending on the loading width [20][21][22]. Through experiments and numerical simulations, it was showed that confinement through geocell effectively increases the stiffness and strength of the ballast and decreases vertical settlement and lateral dispersion [11,23].…”
Section: Introductionmentioning
confidence: 99%